Quality of Higher Education Services and Student Satisfaction: A Study of the Indonesian Student Association in Malaysia - Subekhan, Moch; Supardi, Supardi; Othman, Mohd Syaubari; Mohd Jamil, Mohd Riduan; Hosshan, Hasrul (JURNAL AL-TANZIM, 2025)
This study aims to analyze the dynamics of service quality and student satisfaction in the context of higher education, with a focus on the Indonesian student population in Malaysia. A quantitative approach was used with regression and correlation analysis. The Higher Education Service Quality Model (HESQUAL) was used to measure service quality, while student satisfaction was assessed using the SERVQUAL model. The study's findings indicate that, first, perceived service quality is at a high level (M = 3.98). Second, student satisfaction is at a moderate level (M = 3.66). Third, service quality has a significant positive contribution to student satisfaction (r = 0.358). These results suggest that although higher education institutions offer high-quality services, student satisfaction remains at a moderate level, indicating a need for improvement. Improving service quality is essential to improving student satisfaction. Institutions should focus on specific aspects of service delivery that directly affect student experience. These findings suggest that educational institutions should prioritize enhancing aspects of service reliability, responsiveness, and empathy, while also encouraging further research on non-service factors that collectively impact student satisfaction.